Positive electrode active material, preparation method thereof, positive electrode plate containing positive electrode active material, battery monomer, battery and electric device

CN119234335APending Publication Date: 2024-12-31CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380034661.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-04-28
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

Lithium-ion batteries are facing a shortage of lithium resources, and there is a high content of free alkaline substances on the surface of the cathode active material, which affects the performance of sodium-ion batteries.

Method used

Using sodium-containing layered transition metal oxides as the matrix, the sodium-rich layer, including specific sodium salts, is generated in situ on the surface, reducing the contact between the matrix and the electrolyte, providing an additional sodium source, and improving cycle stability and structural stability. .

Benefits of technology

It improves the energy density and cycle performance of the battery, reduces the probability of excessive release of sodium ions in the positive active material, and extends the cycle life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119234335A_ABST
    Figure CN119234335A_ABST
Patent Text Reader

Abstract

The invention provides a positive electrode active material, a preparation method thereof, and a positive electrode plate, a battery cell, a battery and an electric device containing the positive electrode active material, the positive electrode active material comprises a substrate and a sodium-rich layer generated in situ on the surface of the substrate, the substrate comprises a sodium-containing layered transition metal oxide, the sodium-rich layer comprises one or more of sodium salts represented by a formula (I) and a formula (II), and the sodium-rich layer comprises one or more of sodium salts represented by a formula (I) and a formula (II). M represents an integer from 1 to 8, and n represents an integer from 2 to 20. # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

Positive electrode active material, preparation method thereof, positive electrode sheet, battery cell, battery and electrical device containing the same Technical Field

[0001] The present application relates to a positive electrode active material, a preparation method thereof, and a positive electrode plate, a battery cell, a battery, and an electrical device containing the same. Background Art

[0002] In recent years, batteries have been widely used in energy storage power systems such as hydropower, thermal power, wind power and solar power stations, as well as in power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace and other fields. At present, lithium-ion batteries still occupy the core position of batteries. At the same time, lithium-ion batteries also face great challenges, such as the increasing shortage of lithium resources. Sodium resources are far more abundant than lithium resources, are more widely distributed, and have a much lower cost than lithium. Therefore, sodium-ion batteries have become a new generation of electrochemical systems with great potential to replace lithium-ion batteries. The positive electrode active material is a key factor affecting the performance of sodium-ion batteries. Due to the constraints of the preparation process, there is often a high content of free alkaline substances on the surface of the positive electrode active material, which will affect the performance of the sodium-ion battery. Therefore, effective technical means are needed to improve the performance of the positive electrode active material. The above statements are only used to provide background technical information related to this application and do not necessarily constitute prior art.

[0003] Summary of the Invention

[0004] The present application provides a positive electrode active material, a preparation method thereof, and a positive electrode plate, a battery cell, a battery, and an electrical device containing the same, which can improve the energy density and cycle performance of the battery.

[0005] In a first aspect, the present application provides a positive electrode active material, comprising a substrate and a sodium-rich layer generated in situ on the surface of the substrate, wherein the substrate comprises a sodium-containing layered transition metal oxide, and the sodium-rich layer comprises one or more sodium salts represented by formula (I) and formula (II).

[0006] m represents an integer of 1 to 8, and n represents an integer of 2 to 20.

[0007] The sodium-rich layer in the positive electrode active material provided in the embodiment of the present application is generated in situ on the surface of the substrate, thereby making the sodium salt uniformly dispersed on the surface of the substrate, reducing direct contact between the substrate and the electrolyte, reducing side reactions, and improving the cycle stability of the positive electrode active material. The sodium-rich layer includes one or more of the sodium salts shown in the above formula (I) and formula (II), which can be used as a sodium supplement to provide an additional sodium source during the first cycle charging process of the battery (i.e., the battery formation process) to supplement the active sodium loss during the negative electrode film formation process. Active sodium will gradually be consumed during the battery cycle, and the sodium salts shown in the above formula (I) and formula (II) can also provide excess active sodium to be stored in the negative electrode, supplement the active sodium loss during the battery cycle, reduce the probability of excessive release of sodium ions in the positive electrode active material, thereby improving the structural stability of the positive electrode active material and improving the cycle performance of the battery. The sodium salts represented by formula (I) and formula (II) undergo irreversible desodiumization during the first cycle of battery charging. During the desodiumization process, the sodium salts also decompose to produce carbon dioxide, which is then discharged as a gas. The solids remaining after the sodium salts are desodiumized are mainly attached to the surface of the substrate in the form of a single carbon substance, which improves electronic conductivity, reduces polarization, and reduces direct contact between the substrate and the electrolyte, thereby reducing side reactions and improving the cycle performance of the battery. Therefore, the positive electrode active material provided by the embodiments of the present application can improve the energy density and cycle performance of the battery.

[0008] In any embodiment, the sodium-rich layer comprises one or more of the following sodium salts:

[0009] In any embodiment, the sodium-rich layer comprises one or more of the following sodium salts:

[0010] In any embodiment, the thickness of the sodium-rich layer is denoted as h, and the volume distribution particle size Dv50 of the positive electrode active material is denoted as D, both in nm. Then, 0.005 ≤ h / D ≤ 0.05, and optionally, 0.01 ≤ h / D ≤ 0.025. By adjusting h / D within the above range, the positive electrode active material can have a high gram capacity and high structural stability, thereby enabling the battery to have a high energy density and a long cycle life.

[0011] In any embodiment, the thickness of the sodium-rich layer is 30-120 nm, optionally 40-100 nm. When the thickness of the sodium-rich layer is within the above range, the positive electrode active material can have a high gram capacity and high cycle stability, thereby enabling the battery to have a high energy density and a long cycle life.

[0012] In any embodiment, the volume distribution particle size Dv50 of the positive electrode active material is 2000-8000 nm. When the volume distribution particle size Dv50 of the positive electrode active material is within the above range, it can have a higher gram capacity and a higher compaction density, and can also have good ion transport capability, thereby enabling the battery to have a higher energy density and a longer cycle life.

[0013] In any embodiment, the sodium-rich layer is located on 80%-100% of the surface of the substrate, and optionally 95%-100% of the surface. This can achieve a good sodium replenishment effect, reduce direct contact between the substrate and the electrolyte, reduce side reactions, and improve the cycle stability of the positive electrode active material, thereby improving the cycle performance of the battery.

[0014] In any embodiment, the positive electrode active material includes one or more of an O3 phase, a P2 phase, and a P3 phase.

[0015] In any embodiment, the content of free alkaline substances on the surface of the positive electrode active material is less than or equal to 13%, and can be less than or equal to 3.2%. The low content of free alkaline substances on the surface of the positive electrode active material can make the positive electrode active material have higher interfacial stability, thereby facilitating improved battery cycle performance and / or rate performance, and also facilitating improved processing performance of the positive electrode slurry and battery.

[0016] In any embodiment, the pH of the positive electrode active material is 10.0-13.0, optionally 11.0-12.3. The lower pH of the positive electrode active material can provide the positive electrode active material with higher interfacial stability, thereby improving the cycle performance and / or rate performance of the battery, and also improving the processing performance of the positive electrode slurry and the battery.

[0017] In any embodiment, the carbon content of the positive electrode active material is 1%-13%, optionally 6.3%-8.5%.

[0018] In any embodiment, the sodium-containing layered transition metal oxide includes one or more oxides represented by formula (III), Na x M a A b B c O m Q n Formula (III)

[0019] 0<x≤1, 0<a≤1, 0≤b≤1 / 3, 0≤c≤1 / 3, 1.9≤m≤2, 0≤n≤0.1; M includes one or more of Ni, Mn, Fe, Co, and Cu; A includes one or more metal elements of Group IA, Group IIA, Group IIIA, Group IVA, Group VA, Group IIB, Group IIIB, Group IVB, Group VB, and Group VIB, and optionally includes one or more of Li, K, Mg, Ca, Sr, Ba, Zn, La, Sc, Y, Ti, Zr, V, Nb, Ta, Cr, Mo, W, Al, Sn, Ge, Bi, and Sb; B includes one or more non-metallic elements of Group IIIA, Group IVA, Group VA, and Group VIA, and optionally includes one or more of Si, P, B, S, and Se; Q includes one or more non-metallic elements of Group VA and Group VIIA, and optionally includes one or more of F, Cl, and N.

[0020] A second aspect of the present application provides a method for preparing a positive electrode active material, comprising the following steps:

[0021] Providing a sodium-containing layered transition metal oxide, wherein the surface of the sodium-containing layered transition metal oxide comprises a free alkaline substance, and the alkaline substance comprises sodium hydroxide and / or sodium carbonate;

[0022] A solvent and a first reaction component are provided, wherein the solvent comprises a polar organic solvent, and the first reaction component comprises one or more compounds represented by formula (1) and formula (2).

[0023] m represents an integer from 1 to 8, and n represents an integer from 2 to 20;

[0024] The sodium-containing layered transition metal oxide, the solvent and the first reaction component are mixed so that the free alkaline substances on the surface of the sodium-containing layered transition metal oxide react with the first reaction component to form a sodium salt, and then dried to obtain a positive electrode active material, wherein the positive electrode active material includes a matrix and a sodium-rich layer generated in situ on the surface of the matrix, the matrix includes the sodium-containing layered transition metal oxide, and the sodium-rich layer includes the sodium salt formed by the reaction of the free alkaline substances on the surface of the sodium-containing layered transition metal oxide with the first reaction component.

[0025] The preparation method provided in the embodiment of the present application can reduce the content of free alkaline substances on the surface of the substrate while not easily destroying the bulk structure of the substrate; the preparation method provided in the embodiment of the present application can also generate a uniformly dispersed sodium salt in situ on the surface of the substrate, which can reduce polarization, provide an additional sodium source, and supplement the active sodium loss during the negative electrode film formation process. It can also provide excess active sodium to be stored in the negative electrode to supplement the active sodium loss during the battery cycle. Therefore, the positive electrode active material obtained by the preparation method provided in the embodiment of the present application can improve the energy density and cycle performance of the battery, and can also improve the consistency of the battery.

[0026] In any embodiment, the molar ratio of the first reaction component to the sodium-containing layered transition metal oxide is less than or equal to 0.1:1, and can optionally be 0.02:1 to 0.07:1. When the molar ratio of the first reaction component to the sodium-containing layered transition metal oxide is within the above range, the content of free alkaline substances on the surface of the substrate can be effectively reduced, the positive electrode active material can have an appropriate degree of sodium supplementation, and the positive electrode active material can also have a high gram capacity and high structural stability, thereby enabling the battery to have a high energy density and a long cycle life.

[0027] In any embodiment, the mass ratio of the sodium-containing layered transition metal oxide to the solvent is 10:100 to 25:100, and can optionally be 15:100 to 22:100. When the mass ratio of the sodium-containing layered transition metal oxide to the solvent is within the above range, the content of free alkaline substances on the surface of the substrate can be effectively reduced, the positive electrode active material can have an appropriate degree of sodium supplementation, and the positive electrode active material can also have a high gram capacity and high structural stability, thereby enabling the battery to have a high energy density and a long cycle life.

[0028] In any embodiment, the first reaction component comprises one or more of the following compounds,

[0029] In any embodiment, the first reaction component comprises one or more of the following compounds,

[0030] When the first reactive component is within the above range, it can not only effectively reduce the content of free alkaline substances on the substrate surface, so that the positive electrode active material has an appropriate sodium supplementation level and a high gram capacity, but also reduce the polarization of the positive electrode active material, so that the positive electrode active material has high structural stability. Therefore, when the first reactive component is within the above range, the battery can have a high energy density and a long cycle life.

[0031] In any embodiment, the drying temperature is less than or equal to the boiling point of the polar organic solvent. Optionally, 10° C. ≤ the boiling point of the polar organic solvent - the drying temperature ≤ 30° C. When the drying temperature is within the above range, the content of free alkaline substances on the surface of the substrate can be effectively reduced, the positive electrode active material can have an appropriate sodium supplementation level, and the positive electrode active material can also have a high gram capacity and high structural stability, thereby enabling the battery to have a high energy density and a long cycle life.

[0032] In any embodiment, the drying is spray drying. Spray drying helps to disperse the sodium salt formed after the reaction more evenly on the surface of the substrate and also helps to adjust the content of the sodium salt on the surface of the substrate.

[0033] In any embodiment, the polar organic solvent includes one or more of an alcohol solvent, a ketone solvent, a nitrile solvent, and an ether solvent, and optionally includes one or more of ethanol, methanol, acetone, N-methylpyrrolidone, acetonitrile, tetrahydrofuran, and 1,4-dioxane.

[0034] In any embodiment, the volume fraction of the polar organic solvent is 80% to 100%, based on the total volume of the solvent.

[0035] In any embodiment, the solvent further comprises water, and the volume fraction of the water is less than or equal to 20%, based on the total volume of the solvent.

[0036] In any embodiment, the sodium-containing layered transition metal oxide includes one or more oxides represented by formula (III), Na x M a A b B c O m Q n Formula (III)

[0037] 0<x≤1, 0<a≤1, 0≤b≤1 / 3, 0≤c≤1 / 3, 1.9≤m≤2, 0≤n≤0.1; M includes one or more of Ni, Mn, Fe, Co, and Cu; A includes one or more metal elements of Group IA, Group IIA, Group IIIA, Group IVA, Group VA, Group IIB, Group IIIB, Group IVB, Group VB, and Group VIB, and optionally includes one or more of Li, K, Mg, Ca, Sr, Ba, Zn, La, Sc, Y, Ti, Zr, V, Nb, Ta, Cr, Mo, W, Al, Sn, Ge, Bi, and Sb; B includes one or more non-metallic elements of Group IIIA, Group IVA, Group VA, and Group VIA, and optionally includes one or more of Si, P, B, S, and Se; Q includes one or more non-metallic elements of Group VA and Group VIIA, and optionally includes one or more of F, Cl, and N.

[0038] In any embodiment, the volume distribution particle size Dv50 of the sodium-containing layered transition metal oxide is 2000-8000 nm.

[0039] In any embodiment, the sodium-containing layered transition metal oxide includes one or more of an O3 phase, a P2 phase, and a P3 phase.

[0040] The third aspect of the present application provides a positive electrode plate, comprising a positive electrode current collector and a positive electrode film layer arranged on at least one surface of the positive electrode current collector, wherein the positive electrode film layer comprises the positive electrode active material of the first aspect of the present application or the positive electrode active material prepared by the method of the second aspect of the present application.

[0041] In any embodiment, the content of the positive electrode active material in the positive electrode film layer is 50 wt % to 99 wt %, optionally 85 wt % to 99 wt %, based on the total weight of the positive electrode film layer.

[0042] A fourth aspect of the present application provides a battery cell, comprising the positive electrode sheet according to the third aspect of the present application.

[0043] A fifth aspect of the present application provides a battery, comprising the battery cell of the fourth aspect of the present application.

[0044] A sixth aspect of the present application provides an electrical device comprising the battery of the fifth aspect of the present application.

[0045] The electric device of the present application includes the battery provided by the present application, and thus has at least the same advantages as the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0046] To more clearly illustrate the technical solutions of the embodiments of the present application, the following briefly introduces the drawings required for use in the embodiments of the present application. Obviously, the drawings described below are only some embodiments of the present application. For those skilled in the art, other drawings can be obtained based on the drawings without inventive effort.

[0047] FIG1 is a schematic diagram of a battery cell according to an embodiment of the present application.

[0048] FIG. 2 is an exploded schematic diagram of an embodiment of the battery cell of FIG. 1 .

[0049] FIG3 is a schematic diagram of an embodiment of a battery module of the present application.

[0050] FIG4 is a schematic diagram of an embodiment of a battery pack of the present application.

[0051] FIG. 5 is an exploded schematic diagram of the embodiment of the battery pack shown in FIG. 4 .

[0052] FIG6 is a schematic diagram of an embodiment of an electric device including the battery of the present application as a power source.

[0053] FIG. 7 is an X-ray energy dispersive spectrum (EDS) diagram of the positive electrode active material prepared in Example 2.

[0054] In the accompanying drawings, which are not necessarily drawn to scale, reference numerals are as follows: 1 battery pack, 2 upper housing, 3 lower housing, 4 battery module, 5 battery cell, 51 housing, 52 electrode assembly, 53 cover plate. DETAILED DESCRIPTION

[0055] Below, with appropriate reference to the accompanying drawings, the embodiments of the positive electrode active material, its preparation method, and the positive electrode sheet, battery cell, battery and electrical device containing the same are specifically disclosed. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structures are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following description are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0056] " scope " disclosed in the application is limited in the form of lower limit and upper limit, and given range is limited by selecting a lower limit and an upper limit, and selected lower limit and upper limit define the boundary of special range.The scope that this mode limits can be to include end value or not include end value, and can be combined arbitrarily, and promptly any lower limit can form a scope with any upper limit combination.For example, if the scope of 60-120 and 80-110 is listed for specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected.In addition, if the minimum range value 1 and 2 listed, and if the maximum range value 3,4 and 5 are listed, then the following scope can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5.In the application, unless otherwise specified, numerical range " ab " represents the abbreviation of any real number combination between a and b, and wherein a and b are all real numbers. For example, a numerical range of "0-5" indicates that all real numbers between "0-5" are listed herein, and "0-5" is simply an abbreviation for these numerical combinations. Furthermore, when a parameter is expressed as an integer ≥ 2, this is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0057] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form new technical solutions, and such technical solutions should be considered to be included in the disclosure of the present application.

[0058] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form new technical solutions, and such technical solutions should be deemed to be included in the disclosure of this application.

[0059] Unless otherwise specified, all steps of the present application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), indicating that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0060] Unless otherwise specified, the terms "include" and "comprising" used in this application may be open-ended or closed-ended. For example, "include" and "comprising" may mean that other components not listed may also be included or that only the listed components are included.

[0061] Unless otherwise specified, the term "or" is used in this application to be inclusive. For example, the phrase "A or B" means "A, B, or both A and B." More specifically, the condition "A or B" is satisfied if any of the following conditions are met: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0062] In this application, the terms "plurality" and "multiple" refer to two or more.

[0063] Unless otherwise specified, the terms used in this application have the common meanings that are commonly understood by those skilled in the art.

[0064] Unless otherwise stated, the numerical values ​​of the various parameters mentioned in this application can be measured using various test methods commonly used in the art, for example, they can be measured according to the test methods given in the examples of this application. Unless otherwise stated, the test temperature of each parameter is 25°C.

[0065] Unless otherwise specified, all ratio parameters mentioned in this application are compared in the same units. For example, the ratio of the volume distribution particle sizes of A and B is 1:1, and the units of the volume distribution particle sizes of A and B are the same.

[0066] The battery mentioned in the embodiments of the present application may be a single physical module including one or more battery cells to provide higher voltage and capacity. For example, the battery mentioned in the present application may include a battery cell, a battery module, or a battery pack.

[0067] A battery cell is the smallest unit of a battery, independently capable of charging and discharging. A battery cell can be cylindrical, flat, rectangular, or in other shapes, though this is not a limitation in the present invention. Figure 1 shows a battery cell 5 with a rectangular structure as an example.

[0068] When there are multiple battery cells, the multiple battery cells are connected in series, in parallel, or in mixed series via a busbar. In some embodiments, the battery may be a battery module; when there are multiple battery cells, the multiple battery cells are arranged and fixed to form a battery module. In some embodiments, the battery may be a battery pack, which includes a housing and battery cells, with the battery cells or battery modules housed in the housing. In some embodiments, the housing may serve as part of the vehicle's chassis structure. For example, a portion of the housing may form at least a portion of the vehicle's floor, or a portion of the housing may form at least a portion of the vehicle's crossbeam or longitudinal beam.

[0069] In some embodiments, the battery may be an energy storage device, including an energy storage container, an energy storage cabinet, and the like.

[0070] The battery cells provided in the embodiments of the present application include sodium ion battery cells, sodium metal battery cells, negative electrode-free sodium metal battery cells, etc., which are not limited in the embodiments of the present application.

[0071] A battery cell generally includes an electrode assembly. The electrode assembly generally includes a positive electrode sheet, a negative electrode sheet, and a separator located between the positive and negative electrode sheets. The electrode assembly can be a wound structure or a laminated structure, which is not limited in the present embodiment.

[0072] The battery cell may also include an outer packaging, which can be used to encapsulate the electrode assembly and electrolyte. The outer packaging can be a hard shell, such as a hard plastic shell, aluminum shell, steel shell, etc. The outer packaging can also be a soft package, such as a bag-type soft package. The soft package can be made of plastic, such as one or more of polypropylene (PP), polybutylene terephthalate (PBT), and polybutylene succinate (PBS).

[0073] In some embodiments, as shown in Figure 2, the outer packaging may include a housing 51 and a cover plate 53. The housing 51 may include a bottom plate and side plates connected to the bottom plate, which together form a receiving cavity. The housing 51 has an opening communicating with the receiving cavity, and the cover plate 53 is used to cover the opening, thereby sealing the receiving cavity. The electrode assembly 52 is enclosed in the receiving cavity. The number of electrode assemblies 52 contained in the battery cell 5 can be one or more, and can be adjusted according to needs.

[0074] In some embodiments, battery cells can be assembled into a battery module. The number of battery cells contained in a battery module can be multiple, and the specific number can be adjusted according to the application and capacity of the battery module. Figure 3 is a schematic diagram of a battery module 4 as an example. As shown in Figure 3, in the battery module 4, multiple battery cells 5 can be arranged in sequence along the length of the battery module 4. Of course, they can also be arranged in any other manner. The multiple battery cells 5 can further be fixed by fasteners.

[0075] Optionally, the battery module 4 may further include a housing having an accommodation space, and the plurality of battery cells 5 are accommodated in the accommodation space.

[0076] In some embodiments, the battery modules described above may also be assembled into a battery pack, and the number of battery modules contained in the battery pack may be adjusted according to the application and capacity of the battery pack.

[0077] Figures 4 and 5 are schematic diagrams of an exemplary battery pack 1. As shown in Figures 4 and 5, the battery pack 1 may include a housing and multiple battery modules 4 disposed within the housing. The housing comprises an upper housing 2 and a lower housing 3. The upper housing 2 covers the lower housing 3 and forms an enclosed space for accommodating the battery modules 4. The multiple battery modules 4 may be arranged in any manner within the housing.

[0078] The positive electrode sheet includes positive electrode active materials, and the performance of the positive electrode active materials has a crucial impact on battery performance.

[0079] The positive electrode active material provided in the embodiment of the present application includes a substrate and a sodium-rich layer generated in situ on the surface of the substrate, the substrate includes a sodium-containing layered transition metal oxide, and the sodium-rich layer includes one or more sodium salts represented by formula (I) and formula (II).

[0080] m represents an integer of 1 to 8, and n represents an integer of 2 to 20.

[0081] Sodium-containing layered transition metal oxides typically consist of a transition metal M and six surrounding oxygen atoms forming a MO6 octahedral structure, with sodium ions located between the transition metal layers, forming a layered structure with alternating MO6 transition metal layers and NaO6 sodium layers. During battery charge and discharge, sodium-containing layered transition metal oxides are prone to lattice distortion and phase transition, which hinders the transmission and diffusion of sodium ions. They also cause some sodium ions to become free on the surface of the material, where they react with the electrolyte, resulting in irreversible loss of active sodium and reduced battery cycle stability.

[0082] The sodium-rich layer in the positive electrode active material provided in the embodiment of the present application is generated in situ on the surface of the substrate, thereby making the sodium salt uniformly dispersed on the surface of the substrate, reducing direct contact between the substrate and the electrolyte, reducing side reactions, and improving the cycle stability of the positive electrode active material.

[0083] The sodium-rich layer includes one or more of the sodium salts represented by formula (I) and formula (II) above. This sodium salt can serve as a sodium supplement, providing an additional sodium source during the battery's initial charging cycle (i.e., the battery formation process), thereby replenishing the active sodium lost during the negative electrode film formation process. Therefore, the positive electrode active material provided in the embodiments of the present application can have a higher specific capacity, thereby improving the battery's energy density.

[0084] Active sodium will be gradually consumed during the battery cycle, and the sodium salts represented by the above formula (I) and formula (II) can also provide excess active sodium to be stored in the negative electrode, replenishing the active sodium loss during the battery cycle and reducing the probability of excessive release of sodium ions from the positive electrode active material, thereby improving the structural stability of the positive electrode active material and improving the cycle performance of the battery.

[0085] The sodium salts represented by the above formulas (I) and (II) undergo irreversible sodium removal during the first cycle of battery charging. During the sodium removal process, the sodium salts will also decompose to generate carbon dioxide, which is then discharged in the form of gas. The solids remaining after sodium salt removal are mainly attached to the surface of the substrate in the form of carbon element, which plays a role in improving electronic conductivity, reducing polarization, and reducing direct contact between the substrate and the electrolyte, thereby reducing side reactions and improving the cycle performance of the battery.

[0086] Therefore, the positive electrode active material provided in the embodiments of the present application can improve the energy density and cycle performance of the battery.

[0087] At present, the positive electrode sodium replenishment process usually involves physically mixing a sodium replenisher as an additive with the positive electrode active material, adding it to a solvent to prepare a slurry and positive electrode sheet, and achieving the purpose of sodium replenishment through the first cycle charging process of the battery (i.e., the battery formation process). However, since the amount of sodium replenisher used is usually small, there is uneven mixing when it is physically mixed with the positive electrode active material. At the same time, the density and particle size of the sodium replenisher itself will have a significant impact on the uniformity of the prepared positive electrode slurry and positive electrode sheet, which in turn leads to poor sodium replenishment effect and poor electrochemical performance and consistency of the prepared battery.

[0088] The positive electrode active material provided in the embodiment of the present application includes a matrix and a sodium-rich layer generated in situ on the surface of the matrix, thereby having a better sodium replenishment effect, improving the cycle performance of the battery, and also making the prepared battery have higher consistency.

[0089] In some embodiments, m may represent an integer from 1 to 6, optionally an integer from 1 to 4, and more optionally 1 or 2.

[0090] In some embodiments, n may represent an integer from 2 to 10, optionally an integer from 2 to 6, and more optionally 2 or 3.

[0091] In some embodiments, the sodium-rich layer may include one or more of the following sodium salts:

[0092] Optionally, the sodium-rich layer may include one or more of the following sodium salts:

[0093] In some embodiments, the thickness of the sodium-rich layer is denoted as h, and the volume distribution particle size Dv50 of the positive electrode active material is denoted as D, both in nm, then 0<h / D≤0.05. For example, h / D can be 0.005, 0.008, 0.01, 0.012, 0.015, 0.018, 0.02, 0.022, 0.025, 0.028, 0.03, 0.032, 0.035, 0.038, 0.04, 0.042, 0.045, 0.048, 0.05, or a range consisting of any of the above values. The sodium salt itself has a high voltage platform. Therefore, when its content is high and the sodium-rich layer is thick, the sodium salt itself tends to agglomerate to form large particles, thereby increasing polarization, and may also affect the cycle performance of the battery and increase the gas production of the battery. By adjusting h / D within the above range, the sodium salt is evenly dispersed on the surface of the substrate with a thinner thickness, and the residual carbon after desodiumization of the sodium salt can also improve the conductivity of the positive electrode active material to a certain extent, thereby achieving the effect of sodium supplementation without increasing the gas production of the battery, thereby making the battery have good cycle performance.

[0094] In some embodiments, 0.005 ≤ h / D ≤ 0.05, 0.005 ≤ h / D ≤ 0.04, 0.008 ≤ h / D ≤ 0.03, 0.01 ≤ h / D ≤ 0.025, 0.012 ≤ h / D ≤ 0.022, and 0.016 ≤ h / D ≤ 0.020. By adjusting h / D within the above range, the positive electrode active material can have a high gram capacity and high structural stability, thereby enabling the battery to have a high energy density and a long cycle life.

[0095] In some embodiments, the thickness of the sodium-rich layer can be 30-120 nm, for example, 30 nm, 40 nm, 45 nm, 50 nm, 55 nm, 59 nm, 62 nm, 64 nm, 70 nm, 75 nm, 78 nm, 86 nm, 93 nm, 100 nm, 110 nm, 120 nm, or a range consisting of any of the above values.

[0096] In some embodiments, the thickness of the sodium-rich layer may be 40-100 nm, 59-93 nm, or 64-78 nm.

[0097] When the thickness of the sodium-rich layer is within the above range, the positive electrode active material can have a high gram capacity and high cycle stability, and thus the battery can have a high energy density and a long cycle life.

[0098] The thickness of the sodium-rich layer is well known in the art and can be measured using instruments and methods known in the art. For example, the rolled positive electrode sheet can be cut into square samples of a certain size (e.g., 6 cm x 6 cm) using scissors. This can then be polished using an ion cross-section polisher (e.g., IB-19500CP) to obtain a polished sample with a cut surface. A transmission electron microscope (TEM) image can then be obtained. The thickness of the sodium-rich layer can be measured at 10 randomly selected locations within the image, and the average value can be used as the test result.

[0099] In some embodiments, the volume distribution particle size Dv50 of the positive electrode active material may be 2000-8000 nm. When the volume distribution particle size Dv50 of the positive electrode active material is within the above range, it can have a higher gram capacity and a higher compaction density, and can also have good ion transport capability, thereby enabling the battery to have a higher energy density and a longer cycle life.

[0100] The volume distribution particle size Dv50 of the positive electrode active material is well known in the art and represents the particle size corresponding to the cumulative volume distribution percentage of the material reaching 50%. It can be measured using instruments and methods known in the art. For example, it can be conveniently measured using a laser particle size analyzer in accordance with GB / T 19077-2016. The testing instrument can be a Mastersizer 2000E laser particle size analyzer from Malvern Instruments Ltd. in the UK.

[0101] In some embodiments, the sodium-rich layer may be located on 80%-100% of the substrate surface, optionally 85%-100%, 90%-100%, or 95%-100%. This can achieve a good sodium replenishment effect, reduce direct contact between the substrate and the electrolyte, reduce side reactions, and improve the cycle stability of the positive electrode active material, thereby improving the cycle performance of the battery.

[0102] In some embodiments, the positive electrode active material may include one or more of an O3 phase, a P2 phase, and a P3 phase.

[0103] In some embodiments, the sodium-containing layered transition metal oxide comprises one or more of the oxides represented by formula (III), Na x M a A b B c O m Q n Formula (III)

[0104] 0<x≤1, 0<a≤1, 0≤b≤1 / 3, 0≤c≤1 / 3, 1.9≤m≤2, 0≤n≤0.1; M includes one or more of Ni, Mn, Fe, Co, and Cu; A includes one or more metal elements from Group IA, Group IIA, Group IIIA, Group IVA, Group VA, Group IIB, Group IIIB, Group IVB, Group VB, and Group VIB; B includes one or more non-metal elements from Group IIIA, Group IVA, Group VA, and Group VIA; Q includes one or more non-metal elements from Group VA and Group VIIA.

[0105] Unless otherwise specified, in the above chemical formula, when M is more than two elements, the above-mentioned limitation on the numerical range of a is not only a limitation on the stoichiometric number of each element as M, but also a limitation on the sum of the stoichiometric numbers of each element as M. For example, when M is more than two elements M1, M2...Mn, the stoichiometric numbers a1, a2...an of M1, M2...Mn must each fall within the numerical range of a defined in this application, and the sum of a1, a2...an must also fall within the numerical range. Similarly, in the embodiments of the present application, for the case where other elements are more than two elements, the limitation on the numerical range of their stoichiometric numbers also has the above meaning.

[0106] M may include one or more of Ni, Mn, Fe, Co, and Cu. The sodium-containing layered transition metal oxide may be either a mono-material or a multi-material. "Mono-material" refers to a material containing only one transition metal M, for example, the transition metal M includes one of Ni, Mn, Fe, Co, and Cu. "Multi-material" refers to a material containing at least two transition metals M, for example, the transition metal M includes at least two of Ni, Mn, Fe, Co, and Cu, such as a combination of Mn and Fe, a combination of Mn, Fe, and Ni, a combination of Mn, Fe, and Cu, and the like.

[0107] In some embodiments, 0.5≤x≤1, optionally, 0.66≤x≤1.

[0108] In some embodiments, b is 0.

[0109] In some embodiments, 0<b≤1 / 3.

[0110] In some embodiments, c is 0.

[0111] In some embodiments, 0<c≤1 / 3.

[0112] In some embodiments, b is 0 and c is 0.

[0113] In some embodiments, 0<b≤1 / 3 and 0<c≤1 / 3.

[0114] In some embodiments, 0≤b≤1 / 3, 0≤c≤1 / 3, and 0<b+c≤1 / 3. When the total content of element A and element B is within a suitable range, it helps to further improve the cycle performance and / or rate performance of the battery.

[0115] In some embodiments, A includes one or more elements selected from the group consisting of Li, K, Mg, Ca, Sr, Ba, Zn, La, Sc, Y, Ti, Zr, V, Nb, Ta, Cr, Mo, W, Al, Sn, Ge, Bi, and Sb. This helps improve the structural stability of the positive electrode active material and the cycle performance and / or rate performance of the battery.

[0116] In some embodiments, B includes one or more elements selected from Si, P, B, S, and Se. This helps to improve the structural stability of the positive electrode active material and the cycle performance and / or rate performance of the battery.

[0117] In some embodiments, n is 0.

[0118] In some embodiments, 0<n≤0.1. When the content of element Q is within a suitable range, it helps to further improve the cycle performance and / or rate performance of the battery.

[0119] In some embodiments, Q includes one or more elements selected from F, Cl, and N. This helps to improve the structural stability of the positive electrode active material and helps to improve the cycle performance and / or rate performance of the battery.

[0120] The content of each element in the positive electrode active material can be determined by inductively coupled plasma emission spectroscopy (ICP) in accordance with EPA 6010D-2014.

[0121] It should be pointed out here that the shape of the positive electrode active material is not necessarily spherical, but may also be flaky or irregular; the positive electrode active material may be primary particles or secondary particles, or a mixture thereof.

[0122] The shape of the positive electrode active material can be tested using a scanning electron microscope, for example, according to JY / T010-1996. The testing instrument can be a ZEISS Sigma 300.

[0123] In some embodiments, the content of free alkaline substances on the surface of the positive electrode active material may be less than or equal to 13%, and may optionally be less than or equal to 10.2%, less than or equal to 8.7%, less than or equal to 5.2%, less than or equal to 3.2%, less than or equal to 2.5%, less than or equal to 2.0%, less than or equal to 1.7%, or less than or equal to 1.2%. A low content of free alkaline substances on the surface of the positive electrode active material can provide the positive electrode active material with higher interfacial stability, thereby facilitating improved battery cycle performance and / or rate performance, and also facilitating improved processing performance of the positive electrode slurry and battery.

[0124] The free alkaline substances on the surface of the positive electrode active material mainly refer to NaOH and Na2CO3, which can be detected by potentiometric titration. The content of free alkaline substances on the surface of different types of positive electrode active materials will vary.

[0125] In some embodiments, the pH of the positive electrode active material may be 10.0-13.0, optionally 11.0-12.3. A lower pH of the positive electrode active material can provide the positive electrode active material with higher interfacial stability, thereby improving the cycle performance and / or rate performance of the battery, and also improving the processing performance of the positive electrode slurry and the battery.

[0126] The pH of the positive electrode active material can be tested using a pH meter. For example, the following steps can be used: At 25°C, add an appropriate amount of the positive electrode active material to deionized water (mass ratio of 1:9) to form a solution. After sealing, place the solution on a magnetic stirrer and stir for a period of time (e.g., 30 minutes). After stirring, place the solution in a 25°C water bath and let it stand for a period of time (e.g., 1.5 hours) before testing the pH value.

[0127] In some embodiments, the carbon content of the positive electrode active material may be 1%-13%, optionally 2%-12.7%, 4.2%-10.6%, or 6.3%-8.5%. The carbon content of the positive electrode active material can be tested using a high-frequency infrared carbon-sulfur analyzer (such as the CS996 series), and the test standard can refer to GB / T 20123-2006.

[0128] [Preparation method]

[0129] The present invention also provides a method for preparing the positive electrode active material, comprising the following steps:

[0130] Providing a sodium-containing layered transition metal oxide, wherein the surface of the sodium-containing layered transition metal oxide includes free alkaline substances, and the alkaline substances include sodium hydroxide and / or sodium carbonate;

[0131] A solvent and a first reaction component are provided, wherein the solvent comprises a polar organic solvent, and the first reaction component comprises one or more compounds represented by formula (1) and formula (2).

[0132] m represents an integer from 1 to 8, and n represents an integer from 2 to 20;

[0133] A sodium-containing layered transition metal oxide, a solvent and a first reaction component are mixed so that the free alkaline substance on the surface of the sodium-containing layered transition metal oxide reacts with the first reaction component to form the sodium salt shown in the above formula (I) and formula (II), and then dried to obtain a positive electrode active material, wherein the positive electrode active material includes a matrix and a sodium-rich layer generated in situ on the surface of the matrix, the matrix includes the sodium-containing layered transition metal oxide, and the sodium-rich layer includes the sodium salt formed by the reaction of the free alkaline substance on the surface of the sodium-containing layered transition metal oxide with the first reaction component, as shown in the above formula (I) and formula (II).

[0134] Sodium-containing layered transition metal oxides are usually obtained through a high-temperature sintering process. In order to improve the yield and compensate for the volatilization of Na during high-temperature sintering, an excess of sodium source is usually added during the preparation process. As a result, after the high-temperature sintering process, part of the sodium source will remain on the surface of the positive electrode active material and react with moisture and CO2 in the air to form free alkaline substances such as NaOH and Na2CO3. Alkaline substances cause the positive electrode slurry to easily gel or solidify, affecting the coating performance of the positive electrode slurry and the performance of the battery. In addition, free alkaline substances will continue to react with moisture and CO2 in the air and the electrolyte, hindering the transmission and diffusion of sodium ions, and even causing part of the sodium in the bulk structure of the positive electrode active material to be released, thereby deteriorating the stability of the bulk structure and making the bulk structure of the positive electrode active material prone to irreversible phase change, thereby affecting the capacity of the positive electrode active material and also affecting the preparation and performance of the battery.

[0135] At present, water washing or acid washing processes are usually used to reduce the content of free alkaline substances on the surface of the positive electrode active material. However, this method will reduce the sodium content of the positive electrode active material and irreversibly destroy the bulk structure of the positive electrode active material, thereby reducing the specific capacity of the positive electrode active material and deteriorating the structural stability, which ultimately affects the energy density and cycle performance of the battery.

[0136] The first reaction component includes one or more compounds represented by formula (1) and formula (2), which can react with the free alkaline substances on the surface of the substrate, thereby effectively reducing the content of the free alkaline substances while not easily destroying the bulk structure of the substrate, thereby making the positive electrode active material have higher structural stability.

[0137] The compounds represented by formula (1) and formula (2) contain carbonyl anions, which react with free alkaline substances on the substrate surface to generate sodium salts represented by formula (I) and formula (II) in situ on the substrate surface, and the sodium salts can be evenly dispersed on the substrate surface. The sodium salts represented by formula (I) and formula (II) can be used as sodium supplements to provide an additional sodium source during the first cycle charging process of the battery (i.e., the battery formation process), thereby replenishing the active sodium loss during the negative electrode film formation process; they can also provide excess active sodium for storage in the negative electrode, replenishing the active sodium loss during the battery cycle, and improving the cycle stability of the positive electrode active material. The sodium salts represented by formula (I) and formula (II) undergo irreversible sodium removal during the first cycle charging process of the battery. During the sodium removal process, the sodium salts will also decompose to generate carbon dioxide, which is then discharged in the form of gas. The solids remaining after the sodium salts are removed from the sodium salts are mainly attached to the substrate surface in the form of carbon, which plays a role in improving electronic conductivity, reducing polarization, and reducing direct contact between the substrate and the electrolyte, thereby reducing side reactions and improving the cycle performance of the battery.

[0138] At present, the positive electrode sodium supplementation process is usually to physically mix the sodium supplement agent with the positive electrode active material as an additive, add it to the solvent to prepare the slurry and the positive electrode sheet, and realize the purpose of sodium supplementation through the first cycle charging process of the battery (i.e., the battery formation process). However, since the amount of the sodium supplement agent is usually less, there is an uneven mixing situation when it is physically mixed with the positive electrode active material. At the same time, the density and particle size of the sodium supplement agent itself will have a greater impact on the uniformity of the prepared positive electrode slurry and the positive electrode sheet, thereby resulting in poor sodium supplementation effect and poor electrochemical performance and consistency of the prepared battery. The preparation method provided in the embodiment of the present application can make the sodium salt formed by the reaction uniformly dispersed on the surface of the substrate, thereby having a better sodium supplementation effect, improving the energy density and cycle performance of the battery, and also making the prepared battery have a higher consistency.

[0139] The preparation method provided in the embodiment of the present application can reduce the content of free alkaline substances on the surface of the substrate while not easily destroying the bulk structure of the substrate; the preparation method provided in the embodiment of the present application can also generate a uniformly dispersed sodium salt in situ on the surface of the substrate, which can reduce polarization, provide an additional sodium source, and supplement the active sodium loss during the negative electrode film formation process. It can also provide excess active sodium to be stored in the negative electrode to supplement the active sodium loss during the battery cycle. Therefore, the positive electrode active material obtained by the preparation method provided in the embodiment of the present application can improve the energy density and cycle performance of the battery, and can also improve the consistency of the battery.

[0140] The thickness of the sodium-rich layer on the surface of the matrix of the positive electrode active material and the content of the sodium salt are related to parameters such as the type of the first reaction component, the amount of the three components (i.e., sodium-containing layered transition metal oxide, solvent, and first reaction component), and the drying temperature.

[0141] By adjusting the molar ratio of the first reaction component to the sodium-containing layered transition metal oxide, the reaction rate of the first reaction component and the sodium-containing layered transition metal oxide and the solubility of the generated sodium salt can be adjusted, thereby adjusting the thickness of the sodium-rich layer on the surface of the matrix of the positive electrode active material and the morphology of the sodium-rich layer, and also adjusting the content of the sodium salt and the degree of sodium supplementation of the positive electrode active material.

[0142] When the molar ratio of the first reaction component to the sodium-containing layered transition metal oxide is high, the reaction rate of the first reaction component and the sodium-containing layered transition metal oxide is faster, the solubility of the generated sodium salt in the solvent is higher, and the sodium-rich layer on the surface of the matrix of the obtained positive electrode active material is thicker, thereby reducing the content of free alkaline substances and obtaining a higher degree of sodium replenishment.

[0143] In some embodiments, the molar ratio of the first reaction component to the sodium-containing layered transition metal oxide can be less than or equal to 0.1:1. This can reduce the corrosion of the substrate by the first reaction component and facilitate the formation of a complete sodium-rich layer attached to the substrate surface, thereby reducing direct contact between the substrate and the electrolyte and reducing side reactions, thereby enabling the prepared positive electrode active material to have high structural stability and high gram capacity.

[0144] In some embodiments, the molar ratio of the first reaction component to the sodium-containing layered transition metal oxide can be 0.01: 1 to 0.095: 1, 0.02: 1 to 0.08: 1, 0.02: 1 to 0.07: 1, or 0.03: 1 to 0.06: 1. When the molar ratio of the first reaction component to the sodium-containing layered transition metal oxide is within the above range, the content of free alkaline substances on the surface of the substrate can be effectively reduced, the positive electrode active material can have an appropriate degree of sodium supplementation, and the positive electrode active material can also have a high gram capacity and high structural stability, thereby enabling the battery to have a high energy density and a long cycle life.

[0145] In some embodiments, m may represent an integer from 1 to 6, optionally an integer from 1 to 4, and more optionally 1 or 2.

[0146] In some embodiments, n may represent an integer from 2 to 10, optionally an integer from 2 to 6, and more optionally 2 or 3.

[0147] In some embodiments, the first reaction component may include one or more of the following compounds:

[0148] Alternatively, the first reaction component may include one or more of the following compounds,

[0149] When the first reactive component is within the above range, it can not only effectively reduce the content of free alkaline substances on the substrate surface, so that the positive electrode active material has an appropriate sodium supplementation level and a high gram capacity, but also reduce the polarization of the positive electrode active material, so that the positive electrode active material has high structural stability. Therefore, when the first reactive component is within the above range, the battery can have a high energy density and a long cycle life.

[0150] In some embodiments, the polar organic solvent may include one or more of an alcohol solvent, a ketone solvent, a nitrile solvent, and an ether solvent. Alternatively, the polar organic solvent may include one or more of ethanol, methanol, acetone, N-methylpyrrolidone (NMP), acetonitrile, tetrahydrofuran, and 1,4-dioxane.

[0151] In some embodiments, the volume fraction of the polar organic solvent may be 80% to 100%, based on the total volume of the solvent.

[0152] In some embodiments, the solvent may further include water, and the volume fraction of water is less than or equal to 20%, based on the total volume of the solvent.

[0153] In some embodiments, the mass ratio of the sodium-containing layered transition metal oxide to the solvent can be 10:100 to 25:100, and can optionally be 15:100 to 22:100. When the mass ratio of the sodium-containing layered transition metal oxide to the solvent is within the above range, the content of free alkaline substances on the surface of the substrate can be effectively reduced, the positive electrode active material can have an appropriate degree of sodium supplementation, and the positive electrode active material can also have a high gram capacity and high structural stability, thereby enabling the battery to have a high energy density and a long cycle life.

[0154] The drying method can be any method known in the art, and the present invention is not limited thereto. In some embodiments, the drying method can be spray drying. Spray drying helps to more evenly disperse the sodium salt formed after the reaction on the substrate surface and also helps to adjust the content of the sodium salt on the substrate surface.

[0155] By adjusting the drying temperature, the reaction rate of the first reaction component with the sodium-containing layered transition metal oxide and the solubility of the generated sodium salt can be adjusted, thereby adjusting the thickness of the sodium-rich layer on the surface of the matrix of the positive electrode active material and the morphology of the sodium-rich layer. It is also possible to adjust the content of the sodium salt and the degree of sodium supplementation of the positive electrode active material.

[0156] When the drying temperature is high, the reaction rate of the first reaction component with the sodium-containing layered transition metal oxide is faster, the solubility of the generated sodium salt in the solvent is higher, and the sodium-rich layer on the surface of the matrix of the obtained positive electrode active material is thicker, thereby reducing the content of free alkaline substances and obtaining a higher degree of sodium replenishment.

[0157] In some embodiments, the drying temperature may be less than or equal to the boiling point of the polar organic solvent. Optionally, 10° C. ≤ the boiling point of the polar organic solvent - the drying temperature ≤ 30° C. When the drying temperature is within the above range, the content of free alkaline substances on the surface of the substrate can be effectively reduced, and the positive electrode active material can have an appropriate sodium supplementation level. The positive electrode active material can also have a high gram capacity and high structural stability, thereby enabling the battery to have a high energy density and a long cycle life.

[0158] In some embodiments, the sodium-containing layered transition metal oxide comprises one or more of the oxides represented by formula (III), Na x M a A b B c O m Q n Formula (III)

[0159] 0<x≤1, 0<a≤1, 0≤b≤1 / 3, 0≤c≤1 / 3, 1.9≤m≤2, 0≤n≤0.1; M includes one or more of Ni, Mn, Fe, Co, and Cu; A includes one or more metal elements from Group IA, Group IIA, Group IIIA, Group IVA, Group VA, Group IIB, Group IIIB, Group IVB, Group VB, and Group VIB; B includes one or more non-metal elements from Group IIIA, Group IVA, Group VA, and Group VIA; Q includes one or more non-metal elements from Group VA and Group VIIA.

[0160] Unless otherwise specified, in the above chemical formula, when M is more than two elements, the above-mentioned limitation on the numerical range of a is not only a limitation on the stoichiometric number of each element as M, but also a limitation on the sum of the stoichiometric numbers of each element as M. For example, when M is more than two elements M1, M2...Mn, the stoichiometric numbers a1, a2...an of M1, M2...Mn must each fall within the numerical range of a defined in this application, and the sum of a1, a2...an must also fall within the numerical range. Similarly, in the embodiments of the present application, for the case where other elements are more than two elements, the limitation on the numerical range of their stoichiometric numbers also has the above meaning.

[0161] M may include one or more of Ni, Mn, Fe, Co, and Cu. The sodium-containing layered transition metal oxide may be either a mono-material or a multi-material. "Mono-material" refers to a material containing only one transition metal M, for example, the transition metal M includes one of Ni, Mn, Fe, Co, and Cu. "Multi-material" refers to a material containing at least two transition metals M, for example, the transition metal M includes at least two of Ni, Mn, Fe, Co, and Cu, such as a combination of Mn and Fe, a combination of Mn, Fe, and Ni, a combination of Mn, Fe, and Cu, and the like.

[0162] In some embodiments, 0.5≤x≤1, optionally, 0.66≤x≤1.

[0163] In some embodiments, b is 0.

[0164] In some embodiments, 0<b≤1 / 3.

[0165] In some embodiments, c is 0.

[0166] In some embodiments, 0<c≤1 / 3.

[0167] In some embodiments, b is 0 and c is 0.

[0168] In some embodiments, 0<b≤1 / 3 and 0<c≤1 / 3.

[0169] In some embodiments, 0≤b≤1 / 3, 0≤c≤1 / 3, and 0<b+c≤1 / 3. When the total content of element A and element B is within a suitable range, it helps to further improve the cycle performance and / or rate performance of the battery.

[0170] In some embodiments, A includes one or more elements selected from the group consisting of Li, K, Mg, Ca, Sr, Ba, Zn, La, Sc, Y, Ti, Zr, V, Nb, Ta, Cr, Mo, W, Al, Sn, Ge, Bi, and Sb. This helps improve the structural stability of the positive electrode active material and the cycle performance and / or rate performance of the battery.

[0171] In some embodiments, B includes one or more elements selected from Si, P, B, S, and Se. This helps to improve the structural stability of the positive electrode active material and the cycle performance and / or rate performance of the battery.

[0172] In some embodiments, n is 0.

[0173] In some embodiments, 0<n≤0.1. When the content of element Q is within a suitable range, it helps to further improve the cycle performance and / or rate performance of the battery.

[0174] In some embodiments, Q includes one or more elements selected from F, Cl, and N. This helps to improve the structural stability of the positive electrode active material and helps to improve the cycle performance and / or rate performance of the battery.

[0175] It should be pointed out here that the shape of the sodium-containing layered transition metal oxide is not necessarily spherical, but may also be flaky or irregular; the sodium-containing layered transition metal oxide may be primary particles or secondary particles, or a mixture thereof.

[0176] In some embodiments, the sodium-containing layered transition metal oxide has a volume distribution particle size Dv50 of 2000-8000 nm.

[0177] In some embodiments, the sodium-containing layered transition metal oxide includes one or more of an O3 phase, a P2 phase, and a P3 phase.

[0178] In some embodiments, the sodium-containing layered transition metal oxide can be prepared by methods known in the art, for example, by solid-phase sintering, or can be purchased commercially.

[0179] Unless otherwise specified, all raw materials used in the above preparation methods can be obtained commercially.

[0180] [Positive electrode]

[0181] The embodiment of the present application also provides a positive electrode plate.

[0182] The positive electrode sheet includes a positive electrode current collector and a positive electrode film layer disposed on at least one surface of the positive electrode current collector. The positive electrode film layer includes the positive electrode active material described above in this application or a positive electrode active material prepared by the preparation method described above in this application. The positive electrode current collector has two surfaces that oppose each other in the thickness direction of the positive electrode current collector, and the positive electrode film layer is disposed on either or both of the two opposing surfaces of the positive electrode current collector.

[0183] In some embodiments, the content of the positive electrode active material in the positive electrode film layer is 50 wt % to 99 wt %, optionally 85 wt % to 99 wt %, based on the total weight of the positive electrode film layer.

[0184] The positive electrode film layer may further include other positive electrode active materials known in the art, such as, but not limited to, one or more of fluorides, sulfides, phosphates, pyrophosphates, metal-organic frameworks / metal hexanides, and organic compounds. These other positive electrode active materials may be used alone or in combination of two or more.

[0185] In some embodiments, the positive electrode film layer may further include a positive electrode conductive agent. The present application does not particularly limit the type of the positive electrode conductive agent. As examples, the positive electrode conductive agent may include one or more of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0186] In some embodiments, the positive electrode film layer may further optionally include a positive electrode binder. The present application does not particularly limit the type of positive electrode binder. As an example, the positive electrode binder may include polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, fluorinated acrylic resin, styrene-butadiene rubber (SBR), water-soluble unsaturated resin SR-1B, water-based acrylic resin (e.g., polyacrylic acid PAA, polymethacrylic acid PMAA, sodium polyacrylate PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), carboxymethyl chitosan (CMCS) One or more.

[0187] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. As an example of a metal foil, aluminum foil may be used. The composite current collector may include a polymer material base layer and a metal material layer formed on at least one surface of the polymer material base layer. As an example, the metal material may include one or more of aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver, and silver alloy. As an example, the polymer material base layer may include one or more of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), and polyethylene (PE).

[0188] The positive electrode film is typically formed by coating a positive electrode slurry onto a positive electrode current collector, drying it, and cold pressing it. The positive electrode slurry is typically formed by dispersing the positive electrode active material, an optional conductive agent, an optional binder, and any other components in a solvent and stirring them uniformly. The solvent can be, but is not limited to, N-methylpyrrolidone (NMP).

[0189] [Negative electrode]

[0190] The battery cell includes a negative electrode plate. The structure and composition of the negative electrode plate can be selected according to the type of battery cell, and the embodiments of the present application are not limited thereto.

[0191] In some embodiments, the negative electrode sheet may include a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector and comprising a negative electrode active material. For example, the negative electrode current collector may have two opposing surfaces in its thickness direction, and the negative electrode film layer may be disposed on either or both of the two opposing surfaces of the negative electrode current collector.

[0192] The negative electrode active material may be any material known in the art. For example, the negative electrode active material includes, but is not limited to, one or more of soft carbon, hard carbon, and mesophase microcarbon beads.

[0193] In some embodiments, the negative electrode film layer may further optionally include a negative electrode conductive agent. The present application does not particularly limit the type of the negative electrode conductive agent. As examples, the negative electrode conductive agent may include one or more of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0194] In some embodiments, the negative electrode film layer may further optionally include a negative electrode binder. The present application does not particularly limit the type of the negative electrode binder. As examples, the negative electrode binder may include one or more of styrene-butadiene rubber (SBR), water-soluble unsaturated resin SR-1B, water-based acrylic resin (e.g., polyacrylic acid PAA, polymethacrylic acid PMAA, sodium polyacrylate PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), and carboxymethyl chitosan (CMCS).

[0195] In some embodiments, the negative electrode film layer may further include other additives. For example, the other additives may include a thickener, such as sodium carboxymethyl cellulose (CMC), a PTC thermistor material, and the like.

[0196] The negative electrode film layer is typically formed by coating the negative electrode slurry onto the negative electrode current collector, drying it, and cold pressing it. The negative electrode slurry is typically formed by dispersing the negative electrode active material, an optional conductive agent, an optional binder, and other optional additives in a solvent and stirring them uniformly. The solvent can be, but is not limited to, N-methylpyrrolidone (NMP) or deionized water.

[0197] The negative electrode plate does not exclude other additional functional layers in addition to the negative electrode film layer. For example, in some embodiments, the negative electrode plate may further include a conductive primer layer (e.g., composed of a conductive agent and a binder) disposed on the surface of the negative electrode current collector and sandwiched between the negative electrode current collector and the negative electrode film layer; in some embodiments, the negative electrode plate may further include a protective layer covering the surface of the negative electrode film layer.

[0198] In some embodiments, the negative electrode sheet may include a negative electrode current collector and a metal layer disposed on at least one surface of the negative electrode current collector. The metal material in the metal layer may include one or more of sodium element and sodium alloy.

[0199] A sodium alloy may be an alloy of metallic sodium and other metallic elements or non-metallic elements. For example, the other metallic elements in the sodium alloy may include one or more of tin, zinc, aluminum, magnesium, silver, gold, gallium, indium, and platinum. The non-metallic elements in the sodium alloy may include one or more of boron, carbon, and silicon.

[0200] In some embodiments, the negative electrode sheet may be a sodium sheet (foil) or a sodium alloy sheet (foil).

[0201] In some embodiments, the negative electrode sheet may include only the negative electrode current collector to assemble into a negative electrode-free sodium metal battery cell.

[0202] In some embodiments, the negative electrode current collector may include a metal foil, a three-dimensional porous current collector, or a composite current collector. As examples of metal foils, copper foil, copper alloy foil, nickel foil, and nickel alloy foil may be used. As examples of three-dimensional porous current collectors, copper mesh, nickel mesh, foam copper, and foam nickel may be used. The composite current collector may include a polymer material base layer and a metal material layer formed on at least one surface of the polymer material base layer. As an example, the metal material may include one or more of copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver, and silver alloy. As an example, the polymer material base layer may include one or more of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), and polyethylene (PE).

[0203] [Electrolytes]

[0204] The battery cell includes an electrolyte. This application does not specifically limit the type of electrolyte, and the electrolyte can be selected according to needs. For example, the electrolyte can include one or more selected from solid electrolytes and liquid electrolytes (i.e., electrolytes).

[0205] In some embodiments, the electrolyte is an electrolyte solution including an electrolyte salt and a solvent.

[0206] The type of electrolyte salt is not specifically limited and can be selected according to actual needs. In some embodiments, as an example, the electrolyte salt can include one or more of NaPF6, NaClO4, NaBCl4, NaSO3CF3, and Na(CH3)C6H4SO3.

[0207] The type of solvent is not specifically limited and can be selected according to actual needs. In some embodiments, as an example, the solvent can include ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), ethyl methyl sulfone (EMS) and diethyl sulfone (ESE) One or more.

[0208] In some embodiments, the electrolyte may optionally include additives. For example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, or additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high-temperature performance, and additives that improve battery low-temperature power performance.

[0209] [Isolation film]

[0210] Battery cells using electrolytes, as well as some battery cells using solid electrolytes, may also include a separator. The separator is placed between the positive and negative electrode sheets, primarily to prevent internal short circuits.

[0211] The present application has no particular limitation on the type of isolation membrane, and any known isolation membrane with a porous structure having good chemical stability and mechanical stability can be selected.

[0212] In some embodiments, the material of the isolation membrane may include one or more of glass fiber, non-woven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The isolation membrane may be a single-layer film or a multi-layer composite film. When the isolation membrane is a multi-layer composite film, the materials of each layer may be the same or different.

[0213] The preparation method of battery cells is well known. In some embodiments, the positive electrode sheet, separator, negative electrode sheet and electrolyte can be assembled to form a battery cell. As an example, the positive electrode sheet, separator, and negative electrode sheet can be formed into an electrode assembly through a winding process and / or a lamination process, and the electrode assembly is placed in an outer package, dried and injected with the above-mentioned electrolyte, and then subjected to vacuum packaging, standing, formation, shaping and other processes to obtain a battery cell. Multiple battery cells can also be further connected in series, in parallel or in a mixed connection to form a battery module. Multiple battery modules can also be connected in series, in parallel or in a mixed connection to form a battery pack. In some embodiments, multiple battery cells can also directly form a battery pack.

[0214] Electrical devices

[0215] The present application also provides an electrical device, which includes a battery provided in the present application. The battery can be used as a power source for the electrical device or as an energy storage unit for the electrical device. The electrical device can be, but is not limited to, a mobile device (such as a mobile phone, a tablet computer, a laptop computer, etc.), an electric vehicle (such as a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc.), an electric train, a ship, a satellite, an energy storage system, etc.

[0216] The electrical device can select a specific type of battery, such as a battery cell, a battery module, or a battery pack, according to its usage requirements.

[0217] Figure 6 is a schematic diagram of an exemplary electric device. This device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. To meet the high power and high energy density requirements of this device, a battery pack or battery module may be used.

[0218] As another example, an electric device may be a mobile phone, a tablet computer, a laptop computer, etc. Such an electric device is usually required to be lightweight and thin, and may use a battery cell as a power source.

[0219] Example

[0220] The following examples describe the present disclosure in more detail. These examples are intended to be illustrative only, as various modifications and variations within the scope of the present disclosure will be apparent to those skilled in the art. Unless otherwise stated, all parts, percentages, and ratios reported in the following examples are by mass, and all reagents used in the examples are commercially available or synthesized according to conventional methods and can be used directly without further processing. The instruments used in the examples are commercially available.

[0221] Comparative Example 1

[0222] (1) Preparation of positive electrode active materials

[0223] Na2CO3, Fe2O3, NiO, and MnO2 were weighed according to the molar ratio of Na:Fe:Ni:Mn of 1:0.3:0.3:0.3, and then ball milled to mix them evenly; the ball-milled mixture was placed in a sintering furnace, and heated from 25°C to 800°C at a heating rate of 5°C / min in an air atmosphere and kept at a constant temperature for 15 hours; after the mixture was sintered, it was naturally cooled to 25°C to obtain the layered transition oxide NaFe 1 / 3 Ni 1 / 3 Mn1 / 3 O2, volume distribution particle size Dv50 is 4000nm.

[0224] (2) Preparation of positive electrode sheet

[0225] The positive electrode active material, conductive agent carbon black Super P, and binder polyvinylidene fluoride (PVDF) prepared above were ground and mixed in a weight ratio of 90:10:10, and an appropriate amount of solvent N-methylpyrrolidone (NMP) was added and stirred to obtain a positive electrode slurry. The positive electrode slurry was evenly coated on the positive electrode current collector aluminum foil, and then dried and cold pressed to obtain a positive electrode sheet. The coating amount was 0.27g / 1540.25mm 2 .

[0226] (3) Preparation of negative electrode sheet

[0227] The negative electrode active material hard carbon, conductive agent carbon black Super P, binder styrene butadiene rubber (SBR), and thickener sodium hydroxymethyl cellulose (CMC) are dissolved in deionized water in a weight ratio of 96.2:0.8:0.8:1.2, and the negative electrode slurry is obtained under the action of a vacuum mixer. The negative electrode slurry is evenly coated on the negative electrode current collector copper foil, naturally dried, and then transferred to a 120°C oven for drying for 1 hour. After that, it is cold pressed and cut to obtain the negative electrode sheet. The coating amount is 0.17g / 1540.25mm 2 .

[0228] (4) Preparation of electrolyte

[0229] In an argon atmosphere glove box (H2O < 0.1ppm, O2 < 0.1ppm), ethylene carbonate (EC) and ethyl methyl carbonate (EMC) were mixed in a volume ratio of 3:7, and then NaPF6 was dissolved in the above organic solvent to prepare an electrolyte with a mass fraction of 12.5%.

[0230] (5) Preparation of batteries

[0231] The positive electrode sheet, the separator (a polypropylene film with a thickness of 12 μm), and the negative electrode sheet are stacked and wound in sequence to obtain an electrode assembly; the electrode assembly is placed in an outer package, dried, and then injected with an electrolyte to obtain a battery.

[0232] Comparative Example 2

[0233] Except for the different preparation process of the positive electrode sheet, the preparation process of the battery is the same as that of Comparative Example 1.

[0234] (2) Preparation of positive electrode sheet

[0235] The positive electrode active material prepared in Comparative Example 1, the conductive agent carbon black Super P, the binder polyvinylidene fluoride (PVDF), and the sodium salt N2 (as shown in Table 1) were ground and mixed uniformly according to a weight ratio of 90:10:10:5, and an appropriate amount of solvent N-methylpyrrolidone (NMP) was added and stirred uniformly to obtain a positive electrode slurry. The positive electrode slurry was evenly coated on the positive electrode current collector aluminum foil, and then dried and cold pressed to obtain a positive electrode sheet. The coating amount was 0.27g / 1540.25mm 2 .

[0236] Sodium salt N2 was prepared as follows: 0.01 mol of compound H2 (as shown in Table 1) was dissolved in 30 mL of deionized water as liquid A; 0.08 mol of sodium hydroxide was dissolved in 30 mL of deionized water as liquid B; liquid B was slowly added dropwise to liquid A to form a precipitate, which was then filtered and dried to obtain sodium salt N2.

[0237] Examples 1 to 18

[0238] The preparation process of the battery is the same as that of Comparative Example 1 except that the preparation process of the positive electrode active material is different.

[0239] (1) Preparation of positive electrode active materials

[0240] The layered transition metal oxide NaFe prepared in Comparative Example 1 1 / 3 Ni 1 / 3 Mn 1 / 3 O2 is added to the solvent and the first reaction component shown in Table 1 and Table 2, stirred evenly, and then spray-dried, wherein the outlet temperature (drying temperature) is as shown in Table 2; after the drying, a layered transition metal oxide with the sodium salt shown in Table 1 and Table 2 coated on the surface is obtained. Layered transition metal oxide NaFe 1 / 3 Ni 1 / 3 Mn 1 / 3 The mass ratio of O2 to solvent is 20:100, and the first reaction component reacts with layered transition metal oxide NaFe 1 / 3 Ni 1 / 3 Mn 1 / 3 The molar ratio of O2 is shown in Table 2, and D represents the volume distribution particle size Dv50 of the positive electrode active materials prepared in Examples 1 to 18, in nm.

[0241] Table 1

[0242] Test section

[0243] (1) Thickness test of sodium-rich layer

[0244] Use scissors to cut the positive electrode sheet prepared above into 6 cm × 6 cm square samples, and polish it with an ion cross-section polisher (such as IB-19500CP) to obtain a polished sample with a cut surface; use a transmission electron microscope to obtain a TEM image, randomly select 10 positions from the image to test the thickness of the sodium-rich layer, and take the average value as the test result.

[0245] (2) Test of the content of free alkaline substances on the surface of positive electrode active materials

[0246] At 25 ° C, 20 ± 0.5 g of the positive electrode active material powder prepared above was weighed into a 250 ml iodine volumetric flask, 150 ml of anhydrous ethanol was added and stirred at 1200 RPM for 60 min, sealed and allowed to stand for 10 min; then, a certain amount of filtrate was removed after vacuum filtration using a microporous filter membrane (such as a 0.45 μm polytetrafluoroethylene microporous filter membrane) and titrated with a hydrochloric acid-ethanol standard solution with a concentration of 0.05 mol / L using a potentiometric titrator to obtain the content of free alkaline substances on the surface of the positive electrode active material.

[0247] The free alkaline substances on the surface of the positive electrode active material mainly refer to NaOH and Na2CO3.

[0248] (3) pH value test of positive electrode active material

[0249] At 25°C, 2 g of the prepared positive electrode active material was added to 18 g of deionized water to make a solution. After sealing, the solution was placed on a magnetic stirrer and stirred for 30 min. After the stirring, the solution was placed in a 25°C water bath and allowed to stand for 1.5 h before testing the pH value.

[0250] (4) Carbon content test of positive electrode active material

[0251] Weigh 5 g of the prepared positive electrode active material into a dedicated crucible at 25°C. Add an appropriate amount of flux (e.g., a mixture of pure iron flux, pure tin flux, and pure tungsten flux) and mix thoroughly. Then, use a high-frequency infrared carbon-sulfur analyzer (e.g., CS996 series) to determine the carbon content of the positive electrode active material. The testing standard can refer to GB / T 20123-2006.

[0252] (5) Battery formation and capacity testing

[0253] At 45°C, the prepared battery (the battery without the formation process) was charged at a constant current of 0.05C to 4.2V, and the charging capacity at this time was recorded as C0. After the battery was allowed to stand at 25°C for 5 minutes, it was discharged at a constant current of 0.1C to 1.5V, and the discharge capacity at this time was recorded as D0.

[0254] The first cycle charge capacity (mAh / g) of the positive electrode active material = charge capacity C0 / mass of the positive electrode active material.

[0255] (6) Battery cycle performance test

[0256] At 25°C, the battery after formation and capacity testing in step (5) was charged at a constant current of 0.33C to 4.2V, and then continued to charge at a constant voltage to a current of 0.05C. At this point, the battery was fully charged, and the charge capacity at this time was recorded as C1. After the battery was allowed to stand for 5 minutes, it was discharged at a constant current of 0.33C to 1.5V. The discharge capacity at this time was recorded as D1. The battery was subjected to a cyclic charge and discharge test according to the above method, and the discharge capacity after each cycle was recorded until the discharge capacity of the battery decayed to 80% of D1. The number of cycles at this time was used to characterize the cycle performance of the battery.

[0257] The above test results are shown in Table 2.

[0258] From the test results in Table 2, it can be seen that the positive electrode active material provided in the embodiment of the present application is a layered transition metal oxide with sodium salt generated in situ on the surface. The sodium salt can reduce the content of free alkaline substances on the surface of the positive electrode active material, reduce the pH of the positive electrode active material, and increase the gram capacity of the positive electrode active material, thereby improving the cycle performance of the battery.

[0259] The test results of Examples 1-18 and Comparative Example 2 show that when sodium salt is used as an additive and physically mixed with the positive electrode active material before being added to the solvent to prepare the slurry and positive electrode sheet, the sodium salt's sodium replenishment effect is poor and the battery's cycling performance is poor. This is because the amount of sodium salt used is generally small, resulting in uneven mixing when physically mixed with the positive electrode active material. Furthermore, the sodium salt's density and particle size significantly affect the uniformity of the prepared positive electrode slurry and positive electrode sheet, thereby affecting the sodium replenishment effect and the battery's cycling performance.

[0260] Figure 7 is an X-ray energy dispersive spectrum (EDS) graph of the positive electrode active material prepared in Example 2. The positive electrode active material includes a substrate and a sodium-rich layer generated in situ on the substrate surface. The thickness of the sodium-rich layer is denoted as h. As shown in Figure 7, carbon is evenly distributed on the substrate surface, indicating that the sodium salt in the sodium-rich layer is uniformly attached to the substrate surface. This effectively reduces direct contact between the substrate and the electrolyte, reduces side reactions, and improves the battery's cycling performance.

[0261] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are merely examples, and any embodiments having substantially the same structure and effect as the technical concept within the scope of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the present application, any other embodiments that can be conceived by those skilled in the art and that combine some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A positive electrode active material, comprising a substrate and a sodium-rich layer generated in situ on the surface of the substrate, wherein the substrate comprises a sodium-containing layered transition metal oxide, and the sodium-rich layer comprises one or more of the sodium salts represented by formula (I) and formula (II), m represents an integer of 1 to 8, and n represents an integer of 2 to 20.

2. The positive electrode active material according to claim 1, wherein The sodium-rich layer includes one or more of the following sodium salts: Optionally, the sodium-rich layer comprises one or more of the following sodium salts:

3. The positive electrode active material according to claim 1 or 2, wherein The thickness of the sodium-rich layer is denoted as h, and the volume distribution particle size Dv50 of the positive electrode active material is denoted as D, both in units of nm, then 0.005≤h / D≤0.05, optionally, 0.01≤h / D≤0.

025.

4. The positive electrode active material according to claim 3, wherein The thickness of the sodium-rich layer is 30-120 nm, and can be 40-100 nm; and / or, The volume distribution particle size Dv50 of the positive electrode active material is 2000-8000nm.

5. The positive electrode active material according to any one of claims 1 to 4, wherein The sodium-rich layer is located on 80%-100% of the surface of the substrate, and optionally 95%-100% of the surface; and / or, The positive electrode active material includes one or more of an O3 phase, a P2 phase, and a P3 phase; and / or, The content of free alkaline substances on the surface of the positive electrode active material is less than or equal to 13%, and can be less than or equal to 3.2%; and / or, The pH of the positive electrode active material is 10.0-13.0, and can be 11.0-12.3; and / or, The carbon content of the positive electrode active material is 1%-13%, and can be 6.3%-8.5%.

6. The positive electrode active material according to any one of claims 1 to 5, wherein The sodium-containing layered transition metal oxide comprises one or more of the oxides represented by formula (III), Na x M a A b B c O m Q n Formula (III) 0<x≤1,0<a≤1,0≤b≤1 / 3,0≤c≤1 / 3,1.9≤m≤2,0≤n≤0.1; M includes one or more of Ni, Mn, Fe, Co, and Cu; A includes one or more metal elements from Group IA, Group IIA, Group IIIA, Group IVA, Group VA, Group IIB, Group IIIB, Group IVB, Group VB, and Group VIB, and optionally includes one or more elements from Li, K, Mg, Ca, Sr, Ba, Zn, La, Sc, Y, Ti, Zr, V, Nb, Ta, Cr, Mo, W, Al, Sn, Ge, Bi, and Sb; B includes one or more non-metallic elements of Group IIIA, Group IVA, Group VA, and Group VIA, and optionally includes one or more elements of Si, P, B, S, and Se; Q includes one or more non-metallic elements from Group VA and Group VIIA, and may optionally include one or more elements from F, Cl, and N.

7. A method for preparing a positive electrode active material, comprising the following steps: Providing a sodium-containing layered transition metal oxide, wherein the surface of the sodium-containing layered transition metal oxide comprises free alkaline substances, and the alkaline substances comprise sodium hydroxide and / or sodium carbonate; A solvent and a first reaction component are provided, wherein the solvent comprises a polar organic solvent, and the first reaction component comprises one or more compounds represented by formula (1) and formula (2), m represents an integer from 1 to 8, and n represents an integer from 2 to 20; The sodium-containing layered transition metal oxide, the solvent and the first reaction component are mixed to allow the free alkaline substance on the surface of the sodium-containing layered transition metal oxide to react with the first reaction component to form a sodium salt, and then dried to obtain a positive electrode active material. The positive electrode active material includes a matrix and a sodium-rich layer generated in situ on the surface of the matrix, the matrix includes a sodium-containing layered transition metal oxide, and the sodium-rich layer includes a sodium salt formed by the reaction of free alkaline substances on the surface of the sodium-containing layered transition metal oxide and the first reaction component.

8. The method according to claim 7, wherein: The molar ratio of the first reaction component to the sodium-containing layered transition metal oxide is less than or equal to 0.1:1, and can be 0.02:1 to 0.07:1; and / or, The mass ratio of the sodium-containing layered transition metal oxide to the solvent is 10:100 to 25:100, and can be optionally 15:100 to 22:

100.

9. The method according to claim 7 or 8, wherein: The first reaction component comprises one or more of the following compounds, Optionally, the first reaction component comprises one or more of the following compounds, 10. The method according to any one of claims 7 to 9, wherein: The drying temperature is less than or equal to the boiling point of the polar organic solvent, optionally, 10°C ≤ the boiling point of the polar organic solvent - the drying temperature ≤ 30°C; and / or, The drying is spray drying.

11. The method according to any one of claims 7 to 10, wherein: The polar organic solvent includes one or more of an alcohol solvent, a ketone solvent, a nitrile solvent, and an ether solvent, and optionally includes one or more of ethanol, methanol, acetone, N-methylpyrrolidone, acetonitrile, tetrahydrofuran, and 1,4-dioxane; and / or, The volume fraction of the polar organic solvent is 80% to 100%, based on the total volume of the solvent; and / or, The solvent further includes water, and the volume fraction of the water is less than or equal to 20%, based on the total volume of the solvent.

12. The method according to any one of claims 7 to 11, wherein: The sodium-containing layered transition metal oxide comprises one or more of the oxides represented by formula (III), Na x M a A b B c O m Q n Formula (III) 0<x≤1,0<a≤1,0≤b≤1 / 3,0≤c≤1 / 3,1.9≤m≤2,0≤n≤0.1; M includes one or more of Ni, Mn, Fe, Co, and Cu; A includes one or more metal elements from Group IA, Group IIA, Group IIIA, Group IVA, Group VA, Group IIB, Group IIIB, Group IVB, Group VB, and Group VIB, and optionally includes one or more elements from Li, K, Mg, Ca, Sr, Ba, Zn, La, Sc, Y, Ti, Zr, V, Nb, Ta, Cr, Mo, W, Al, Sn, Ge, Bi, and Sb; B includes one or more non-metallic elements of Group IIIA, Group IVA, Group VA, and Group VIA, and optionally includes one or more elements of Si, P, B, S, and Se; Q includes one or more non-metallic elements from Group VA and Group VIIA, and may optionally include one or more elements from F, Cl, and N.

13. The method according to any one of claims 7 to 12, wherein: The volume distribution particle size Dv50 of the sodium-containing layered transition metal oxide is 2000-8000 nm; and / or, The sodium-containing layered transition metal oxide includes one or more of an O3 phase, a P2 phase, and a P3 phase.

14. A positive electrode sheet, comprising a positive electrode current collector and a positive electrode film layer disposed on at least one surface of the positive electrode current collector, wherein: The positive electrode film layer comprises the positive electrode active material according to any one of claims 1 to 6 or the positive electrode active material prepared by the method according to any one of claims 7 to 13.

15. The positive electrode sheet according to claim 14, wherein: The content of the positive electrode active material in the positive electrode film layer is 50 wt % to 99 wt %, and optionally 85 wt % to 99 wt %, based on the total weight of the positive electrode film layer.

16. A battery cell comprising the positive electrode sheet according to claim 14 or 15.

17. A battery comprising the battery cell according to claim 16.

18. An electrical device comprising the battery according to claim 17.